UPAYA GURU DALAM MENANGGULANGI KENAKALAN SISWA SDN 09 PANGGANG JEPARA - Rizqon Mahmud; Much Arsyad Fardani; Lintang Kironoratri (Universitas Muria Kudus, 2025)
This study aims to determine the types of student delinquency and teacher effort in responding to and handling student delinquent behavior at SDN 09 Panggang Jepara. The research method uses descriptive qualitative. The subject of the study was SDN 09 Panggang Jepara. Data collection techniques were interviews, observation, and documentation. Data analysis used data collection, data presentation, data reduction, and data conclusion. The results of the study showed that the types of student delinquency were divided into three levels, namely mild delinquency, moderate delinquency, and severe delinquency. The strategies used by teachers in overcoming student delinquency differ according to the level of student delinquency. The strategies used are by making policies to be obeyed together, instilling positive cultural habits, implementing preventive efforts with consistent rules, repressive efforts by implementing a triangle of restitution in handling problems, and curative efforts by paying special attention to students who commit delinquency. The conclusion of the study with the existence of teacher strategies in overcoming delinquency makes students more careful, does not repeat, and students obey teachers.